Exploration of Microalgal Role as Bioindicator to Evaluate Water Quality in the Waters of Desa Sungai Nibung West Kalimantan - Ikha Safitri; Mega Sari Juane Sofiana (Postgraduate, University of Mataram, 2024)
The coastal area of Desa Sungai Nibung is a conservation area with high biodiversity. This area has been used for various activities, such as capture and aquaculture fisheries, shipping traffic, and tourism. These activities could affect the waters, ecosystems, and biodiversity condition. Water quality is determined by several parameters, which one of the bioindicators is microalgae. The presence of certain microalgae contributes to the change in the color of the water which indicates the presence of HABS phenomenon. Therefore, this study aimed to determine the composition of microalgae in the waters of Desa Sungai Nibung. Water samples were taken by purposive sampling method in 5 stations with different environmental characteristics. Each station was taken surface water using a plankton net. Microalgae in the samples were then observed with a microscope and their abundance was calculated. The composition of microalgae consisted of 22 genera, belonging to Bacillariophyceae (14 genera), Dinophyceae (7 genera), and Chlorophyceae (1 genus). The Bacillariophyceae dominated the waters with a percentage of 63.66%. Microalgae abundance ranged from 3.94-7,329.25 ind/L with oligotrophic and mesotrophic categories. The diversity index was low to medium (0.74-1.78), Evenness index was low to medium (0.31-0.66), and dominance index was low to high (0.24-0.74).